Nurses Perception of Family Health Strategy in the care provided to elderly people with depression (Research, Society and Development, 2022)
Objective: reveal the perception of nurses from the Family Health Strategy about the nursing care provided to the elderly with depressive symptoms. Methodology: qualitative approach study with 33 higher-level nursing professionals from family health teams in the urban area, based on the Collective Subject Discourse methodology, between August and September 2021. For data analysis, analysis was carried out thematic. Results: female professionals prevailed (87.9%), with a mean age of 39.6 years. Regarding the speeches, 4 thematic categories were identified: Knowledge and training for the management of elderly patients with depressive symptoms; Facilities and difficulties in caring for the elderly with depressive symptoms; Strategies for coping with depression in the elderly, and Main signs perceived by nursing professionals in relation to depression in the elderly. Final Considerations: there are still weaknesses in the care of the elderly with depressive symptoms in Primary Care. In this context, the role of nursing in periods of depression in the elderly is essential, as these professionals have specific strategies for beneficial actions in this scenario.